Berberine-Incorporated Shape Memory Fiber Applied as a Novel Surgical Suture - Zhou, Wen-cheng; Tan, Peng-fei; Chen, Xing-han; Cen, Ying; You, Chao; Tan, Lin; Li, Hao; Tian, Meng (Frontiers in Pharmacology, 2020)
The surgical suture has long been used to reconnect the injured tissues to restore their structure and function. However, its utility remains challenging in many areas such as surgical site infections and minimally invasive surgeries. Herein, we report a novel surgical suture that possesses both antibacterial activity and shape memory effect to address these issues. In detail, natural anti-bacterial berberine was incorporated directly into the spinning solution of shape memory polyurethane with a near body transition temperature, and then berberine-containing polyurethane (BP) fibers were prepared by a facile one-step wet-spinning method for surgical suture. The prepared BP fibers were micro-sized and characterized by their transition temperature, morphology, water contact angles, mechanical properties, in vitro shape memory effect, drug release, and antibacterial activity. The results showed that with the increasing amount of the incorporated berberine, the transition temperatures of the fibers were not significantly affected, remains at near body temperature, while the contact angles of the fibers were significantly decreased and the mechanical properties of the fibers were significantly weakened. The optimized fiber was selected to evaluate the cytotoxicity and in vivo biocompatibility before in vivo shape memory effect and wound healing capacity in a mouse skin suture-wound model was tested. Besides the shape memory effect, it was demonstrated that the fiber is capable of antibacterial activity and anti-inflammatory, and promoting wound healing. The mechanism of antibacterial activity and anti-inflammatory of the fiber was discussed. Overall, it is expected that by the berberine added to the fiber for surgical suture, it will be more popular and extend the utility of the sutures in a wide range of clinical applications.